ANALISIS KEBIJAKAN PEMBERDAYAAN DAN PERLINDUNGAN SOSIAL PADA KELOMPOK LANJUT USIA (LANSIA) - Nadia Anggraini (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2018)
The right to social security is one of the rights of citizens, as well as the elderly (elderly) also have the same rights as other residents. Elderly people who are left without social security, for example without health insurance are vulnerable to being a burden on society. The aim is to analyze the elderly population in Indonesia and efforts to improve their social welfare. From various sources of the elderly population and its social security policies in Indonesia. Calculated Source of Elderly Population in Indonesia Spending quite dramatically over the past 30 years. There are four diseases that are very difficult with the aging process, namely: impaired blood circulation, hormonal disorders, disorders of the joints, and various kinds of neoplasms. Efforts to improve social welfare for the elderly organized by the Government include: social protection, social assistance, social care, and empowerment. Therefore, social responsibility for the elderly is still limited because the focus is only on neglected elderly people, and the agreement has not been optimal for the approval of all elderly people's land in Indonesia. Support from the family and community is a supporting factor for the elderly to always be enthusiastic in participating in activities. With the help of increasing social welfare for the elderly. Recommendations for the Government to consistently support the improvement of welfare for the elderly, thereby supporting healthy aging and active aging.